U.S. Cultural Exchange Programs in Algeria: Opportunities and Challenges - Oumeddour, Soror (The Journal of US-Africa Studies, 2023)
The internationalization of the higher education sector in Algeria is one of the government’s most important priorities to catch up with the contemporary trends towards fostering internationalization in higher education in the twenty-first century globalized world. The U.S. Embassy in Algeria has added a valuable support instrument in this respect through its cultural exchange programs. Ongoing programs of scholarships for students’ mobility based on the strategies that aim at strengthening the universities’ international dimension have been created. The U.S. Embassy in Algiers provides different types of programs which are perceived as useful and important as they create further opportunities for the learners and the institutions to open up to the increased international environment of the higher education sector. Nevertheless, there seems to be major challenges and hindrances limiting its full potential as a strong tool for sustainable development and better higher education quality. As a strategic soft power tool with longterm impact, American cultural exchange programs seek to Americanize the world via spreading the American values, principles, and ideals abroad through impressing the program participators with the American culture and ideologies. In other words, the Americans assign to themselves the role of reinforcing and supervising peace and democracy in the world. To achieve that, they use the various cultural and educational exchange programs as a soft power mechanism to promote and emphasize the superiority of the American system, ideology, and identity in the world. The seriousness of these programs lies in the pre-selection of the participants. They select the youth with a special focus on their abilities to affect and influence others, along with the potentials they have to be future leaders in their countries to pursue and reinforce the American interests. Ideologies are associated with power structures. Indeed, American Policymakers rely on cultural exchange programs to fashion an international atmosphere that is supportive and conducive to the U.S. interests and values worldwide. Keywords: Algeria, Cultural Exchange Programs, Higher Education, United States.